Neutralization of CD95 ligand promotes regeneration and functional recovery after spinal cord injury - Demjen, Deana; Kleber, Susanne; Zuliani, Cecilia; Stieltjes, Bram; Walczak, Henning; Essig, Marco; Edler, Lutz; Krammer, Peter H.; Martín-Villalba, Ana (Nature medicine, 2004)
The clinical outcome of spinal cord injury (SCI) depends in part on the extent of secondary damage, to which apoptosis contributes. The CD95 and tumor necrosis factor (TNF) ligand/receptor systems play an essential role in various apoptotic mechanisms. To determine the involvement of these ligands in SCI-induced damage, we neutralized the activity of CD95 ligand (CD95L) and/or TNF in spinal cord-injured mice. Therapeutic neutralization of CD95L, but not of TNF, significantly decreased apoptotic cell death after SCI. Mice treated with CD95L-specific antibodies were capable of initiating active hind-limb movements several weeks after injury. The improvement in locomotor performance was mirrored by an increase in regenerating fibers and upregulation of growth-associated protein-43 (GAP-43). Thus, neutralization of CD95L promoted axonal regeneration and functional improvement in injured adult animals. This therapeutic strategy may constitute a potent future treatment for human spinal injury.
Gesehen am 06.04.2021